Environment-friendly easy-to-process ceramic rock plate with low crystal silicon dioxide content and production method thereof
Patent Information
- Application Number
- CN202411321879.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-09-23
AI Technical Summary
[0005]为了解决现有陶瓷岩板生产制造、加工过程中因晶体二氧化硅含量高导致矽肺病致病风险高以及后期冷加工破损率高的问题,本发明提供了一种低晶体二氧化硅含量环保型易加工陶瓷岩板及其生产方法
(1)本发明通过低晶体二氧化硅含量陶瓷岩板坯体配方体系创新设计和烧成制度联动高效调控,生产出的低晶体二氧化硅含量环保型易加工陶瓷岩板的坯体层的物相组成中晶体二氧化硅SiO2(Cp)由重量百分比计的含量≤10%,实现陶瓷岩板生产过程产生的粉尘中晶体二氧化硅含量大幅减少,以及生产出的陶瓷岩板的坯体层物相组成中晶体二氧化硅含量大幅降低,有效降低了陶瓷岩板生产、加工等过程中罹患矽肺病的风险,顺应国家绿色、健康、环保生产的号召;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of building ceramics, specifically to an environmentally friendly, easy-to-process ceramic slab with low crystalline silica content and its production method. Background Technology
[0002] Compared to traditional porcelain tiles, ceramic slabs, a new type of ceramic decorative product in recent years, have the characteristics of larger size, fewer gaps, better density, stronger mechanical properties, and richer and more realistic surface textures. Therefore, ceramic slabs have a wider range of applications than traditional porcelain tiles. They can not only be used as wall and floor tiles, but also as a multi-functional decorative material. Through secondary processing such as cutting and drilling, they can be made into different shapes and sizes and applied to different areas of the home, such as dining tables, coffee tables, wardrobes, cabinet doors, and background walls.
[0003] However, current ceramic slab blanks use quartz, clay, and feldspar as the main raw materials. The content of crystalline silica in the phase composition of these raw materials is generally between 20% and 40% by weight. However, the content of crystalline silica in the phase composition of the produced ceramic slab products is generally higher than 10% by weight. Whether in the early stage of raw material processing of ceramic slab blanks or in the later stage of cutting and polishing ceramic slab products, a large amount of respirable dust with high crystalline silica content will be generated. This dust can be deposited in the lungs, causing characteristic inflammatory reactions, extensive nodular fibrosis of lung tissue, and agglomeration into fibrous masses, commonly known as silicosis. It is often accompanied by emphysema and bullae, making the ceramic industry a high-risk industry for silicosis. Furthermore, since the birth of ceramic slabs, the entire ceramic slab industry has suffered from post-processing cold cracking, with losses reaching 5%-8%. This is one of the main reasons why the production cost of ceramic slabs has remained high, becoming a major pain point in the industry. It restricts the application of ceramic slabs in many fields, affecting their promotion and future development. The main reason for this phenomenon is that the raw materials contain a large amount of crystalline silica, and during the firing process, the crystalline silica undergoes a crystal transformation, generating significant stress. Because ceramic slabs are large in size, the absolute value of residual stress after cooling is also large, making them extremely prone to cracking during production, cutting, and processing.
[0004] Based on this, the present invention provides an environmentally friendly and easily processed ceramic slab with low crystalline silica content and its production method, which significantly reduces the crystalline silica content in the dust generated during the production process of ceramic slabs, and significantly reduces the crystalline silica content in the phase composition of the green body layer of the produced ceramic slabs. This effectively reduces the risk of silicosis during the production and processing of ceramic slabs, while also reducing the stress caused by the crystal transformation of silica in the ceramic slabs, improving the machinability of the ceramic slabs, and thus reducing the losses caused by cold working cracks in the later stages of ceramic slab production. Summary of the Invention
[0005] To address the problems of high risk of silicosis and high breakage rate during cold processing caused by high crystalline silica content in existing ceramic slab production and manufacturing processes, this invention provides an environmentally friendly and easy-to-process ceramic slab with low crystalline silica content and its production method.
[0006] This invention achieves efficient control through innovative design and firing regime linkage of a ceramic slab body formulation system with low crystalline silica content. On the one hand, it minimizes the introduction of crystalline silica SiO2 (C) into the raw materials of the ceramic slab body formulation. r On the other hand, it allows a small amount of crystalline silicon dioxide (SiO2) (C) to be introduced into the raw materials. r During the firing process of the ceramic slab, as much as possible is transformed into amorphous silica and silica that exists as a component in other crystalline phases besides crystalline silica. Amorphous silica is in a glassy state, coating the surface of some crystalline phases (calcium feldspar, sodium feldspar, mullite, cordierite, corundum, etc.), and together with other glassy and gaseous phases, it constitutes the microstructure of the ceramic slab. The crystalline silica SiO2 (C) in the ceramic slab layer is the most abundant component of the ceramic slab. p Reducing the content of silica by weight percentage to 10% or less can effectively reduce the risk of silicosis during the production, polishing, and cutting of ceramic slabs. In addition, it reduces the stress caused by the crystal transformation of silica during firing, resulting in lower residual stress in the finished ceramic slabs, which improves the workability of the slabs and reduces the losses caused by cold working cracks.
[0007] In a first aspect, the present invention provides an environmentally friendly and easy-to-process ceramic slab with low crystalline silica content.
[0008] An environmentally friendly, easy-to-process ceramic slab with low crystalline silica content includes a body layer and a decorative layer disposed on the upper surface of the body layer. The body layer contains crystalline silica SiO2 (C2O3) in its phase composition. p The content, expressed as a percentage by weight, is ≤10%.
[0009] The phase composition refers to the weight percentage content of crystalline phase, glassy phase, and gaseous phase in the ceramic slab body layer. The crystalline phase is the dominant phase determining the basic properties of the ceramic slab, including crystalline silica, anorthite, sodium feldspar, mullite, cordierite, and corundum, etc. Its type, content, and mode of existence affect the performance of the ceramic slab. The glassy phase refers to the low-melting-point components in the ceramic slab body layer; its content and distribution affect the performance of the ceramic slab. The gaseous phase (pores) is unavoidable during the production of ceramic slabs, generally present in very small amounts in the ceramic slab body layer; its mode of existence, content, and distribution also affect the performance of the ceramic slab.
[0010] In this application, crystalline silicon dioxide refers to silicon dioxide existing in crystalline form in the phase composition of ceramic slab raw materials or ceramic slab blanks. The silicon dioxide existing in crystalline form in the phase composition of ceramic slab raw materials is denoted as SiO2(C). r The phase composition of the ceramic slab body layer contains silicon dioxide in crystalline form, denoted as SiO2 (C). p ).
[0011] As a further embodiment, the chemical composition of the blank layer by weight percentage includes: SiO2(T) 58%-65%, Al2O3 22%-28.5%, Fe2O3 0-3%, CaO 0.5%-7%, MgO 0.5%-5%, K2O 1.5%-5%, Na2O 0.35%-3%, with the balance being impurities.
[0012] In this application, SiO2(T) refers to the sum of silicon dioxide in the ceramic slab body layer in the form of crystalline phase, silicon dioxide in the form of glassy phase, and silicon dioxide in the form of components in other crystalline phases besides crystalline silicon dioxide.
[0013] As a further embodiment, the glass phase content in the phase composition of the preform layer is 69.0%-88.5% by weight.
[0014] As a further embodiment, the glass phase in the preform layer comprises, by weight percentage, the following chemical composition: SiO2(A) 59.98%-67%, Al2O3 20.82%-27%, Fe2O3 0-2.64%, CaO 0.65%-5.85%, MgO 0.57%-6.49%, K2O 1.95%-6.26%, Na2O 0.5%-3.76%, and TiO2 0-0.78%.
[0015] In this application, SiO2(A) refers to the content of amorphous silica in the glass phase of the ceramic slab body layer, expressed as a normalized weight percentage.
[0016] Specifically, the SiO2(A) comes from the melting of crystalline silica and feldspar during the firing of the ceramic slab blank, and from the decomposition of clay minerals such as kaolin in the raw materials of the ceramic slab blank during the firing process.
[0017] As a further embodiment, the percentage of silica (SiO2(E)) in the glass phase of the preform layer exceeding the feldspar stoichiometry is ≥27.0%.
[0018] SiO2(E) refers to the percentage of silica in the glass phase of a ceramic slab body that exceeds the stoichiometric ratio of feldspar, including the portion of crystalline silica dissolved from the raw materials into the glass phase and the portion introduced by the decomposition of clay minerals, etc.
[0019] As a further embodiment, the phase composition of the preform layer includes a glass phase with n(CaO+MgO) / n(CaO+MgO+K2O+Na2O)≥0.350.
[0020] In this application, n(CaO+MgO) refers to the sum of the normalized percentages of CaO and MgO in the glass phase of the ceramic slab body layer, expressed as a percentage of substance; n(CaO+MgO+K2O+Na2O) refers to the sum of the normalized percentages of CaO, MgO, K2O, and Na2O in the glass phase of the ceramic slab body layer, expressed as a percentage of substance.
[0021] In the building ceramics industry, CaO and MgO are generally used as excellent fluxes, mainly to reduce the maximum firing temperature of the brick blank and to reduce the high-temperature viscosity and surface tension of the melt. This application, through an innovative design of a low-crystalline silica content ceramic slab body formulation system, increases the proportion of alkaline earth metal oxides (CaO and MgO) in the glass network modifier (CaO, MgO, K2O, and Na2O). This prevents the ceramic slab from underfiring due to excessively high temperatures or overfiring due to excessively low temperatures, and increases the flux content of the ceramic slab body layer. This, in turn, increases the solubility of glass relative to crystalline silica in the phase composition of the body layer during the firing process of the ceramic slab, allowing the small amount of crystalline silica SiO2 (C2O2) introduced from the raw materials to be absorbed more readily. r More of it is converted into amorphous silicon dioxide and silicon dioxide existing as a component in other crystalline phases besides crystalline silicon dioxide, effectively reducing the amount of crystalline silicon dioxide SiO2 (C) in the phase composition of the green body layer. pThe content of ) increases the content of glass phase in the phase composition of the green body layer, and consequently increases the percentage of silica in the glass phase of the green body layer that exceeds the amount provided by the feldspar stoichiometry.
[0022] As a further improvement, the fracture toughness of the low-crystalline silica content, environmentally friendly, and easily processed ceramic slab is ≥1.2 MPa·m. 1 / 2 The modulus of fracture is ≥50MPa.
[0023] As a further option, the environmentally friendly and easy-to-process ceramic slab with low crystalline silica content is processed according to the processability test method in the T / CBCSA 40—2021 "Ceramic Slab" standard to achieve first-level processability.
[0024] Secondly, the present invention provides a method for producing environmentally friendly and easily processed ceramic slabs with low crystalline silica content, comprising the following steps: S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab blank powder: The ceramic slab blank slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab blank powder for pressing ceramic slab blanks. The chemical composition of the ceramic slab blank powder, by dry weight percentage, includes: SiO2 55.68%-62%, Al2O3 20.5%-27.36%, Fe2O3 0-2.88%, CaO 0.48%-6.52%, MgO 0.47%-4.8%, K2O 1.44%-4.8%, Na2O 0.33%-2.8%, loss on ignition 4%-7%, and the balance being impurities. S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain the ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blank: The decorated ceramic slab blank obtained in step S4 is fired at high temperature to obtain a ceramic slab semi-finished product. The highest firing temperature of the high temperature firing is 1150-1250℃, the firing cycle is 55-150min, and the holding time at the highest firing temperature is ≥7min. S6, Post-processing of ceramic slab semi-finished product: The ceramic slab semi-finished product is post-processed to obtain a finished ceramic slab containing a green body layer and a decorative layer disposed on the upper surface of the green body layer. The phase composition of the green body layer is crystalline silicon dioxide SiO2 (C p The content, expressed as a percentage by weight, is ≤10%.
[0025] As a further embodiment, in step S1, when preparing the black ceramic slab slurry, the raw materials for preparing the ceramic slab slurry are multiple of the following: spherical clay A, washed clay A, washed clay B, kaolin A, calcined clay A, potassium feldspar A, potassium feldspar B, potassium-sodium feldspar A, potassium-sodium feldspar B, wollastonite A, raw talc A, raw talc B, calcined bauxite B, and diopside; when preparing the white ceramic slab slurry, the raw materials for preparing the ceramic slab slurry are multiple of the following: spherical clay B, rock mud, kaolin B, calcined clay B, raw talc B, wollastonite A, wollastonite B, potassium feldspar A, potassium feldspar B, pyrophyllite, TM2106 frit, fused silica, calcined alumina A, calcined alumina B, bone ash, calcined bauxite A, and calcined bauxite B.
[0026] As a further option, in step S1, the ball milling system is an intermittent ball milling system or a continuous ball milling system.
[0027] As a further option, in step S2, before spray drying the ceramic slab slurry obtained in step S1, the ceramic slab slurry is subjected to slurry preheating treatment.
[0028] Specifically, preheating the ceramic slab slurry refers to the process of transporting the ceramic slab slurry to a slurry servo tank before spray drying, and heating it to above 80°C through hot air and a slurry gas / liquid heat exchanger in the cold section of the kiln tail. Preheating the ceramic slab slurry can improve its temperature and fluidity, thereby reducing energy consumption in the spray drying process in step S2, improving energy utilization efficiency, increasing production capacity, and achieving the goal of energy conservation and consumption reduction.
[0029] As a further option, in step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0030] As a further option, in step S1, the sieving is performed using an 80-150 mesh vibrating screen, the processing fineness of the ceramic slab slurry is 2.5%-3.5% residue on a 325 mesh sieve, the specific gravity is 1.68-1.74 g / ml, and the flow rate is 16-32 s using an NK-2 Iwata viscosity cup.
[0031] As a further embodiment, in step S2, the moisture content of the ceramic slab blank powder is 5.5%-7.5%, and the particle size is 45%-55% residue on a 40-mesh sieve.
[0032] As a further option, in step S3, the pressing pressure of the molding equipment is 35-42 MPa.
[0033] Residual stress is a key factor affecting the machinability of ceramic slabs. Minimizing residual stress reduces the risk of cracking during production and cutting, resulting in ceramic slabs with excellent machinability. The maximum firing temperature for the ceramic slab body is 1150-1250℃, with a firing cycle of 55-150 minutes and a holding time at the maximum firing temperature ≥7 minutes. Compared to traditional porcelain tiles, this extends the holding time at the maximum firing temperature and slows down the heating and cooling rates. Slowing down the heating rate and extending the holding time at the maximum firing temperature facilitates the introduction of small amounts of crystalline silicon dioxide (SiO2) from the raw materials. r The transformation of silica into the glassy phase and other crystalline phases besides crystalline silica, which exist as components, reduces the amount of crystalline silica SiO2 (C) originally introduced into the raw material. r Further reducing [the amount of silica]; on the other hand, it is beneficial to the oxidative decomposition of humus in the ceramic slab body, thereby increasing the density of the body layer and improving the fracture toughness of the ceramic slab. Delaying the heating and cooling rates can extend the range of crystalline silica transformation in the body layer and make the transformation slow and uniform, reducing the volume effect caused by crystalline silica transformation during firing, allowing the internal stress in the body layer to be completely released, thus effectively reducing residual stress in the body layer. In addition, the ceramic slab body itself has a low crystalline silica content, and during firing, some crystalline silica is transformed into the glass phase and other crystalline phases that exist as components of silica. Therefore, the absolute value of residual stress after cooling is also small, making it less prone to cracking during production, cutting, and processing, and exhibiting excellent machinability. Processing was performed according to the machinability test methods in the T / CBCSA 40—2021 "Ceramic Slab" standard, achieving Level 1 machinability.
[0034] As a further embodiment, the chemical composition of the blank layer by weight percentage includes: SiO2(T) 58%-65%, Al2O3 22%-28.5%, Fe2O3 0-3%, CaO 0.5%-7%, MgO 0.5%-5%, K2O 1.5%-5%, Na2O 0.35%-3%, with the balance being impurities.
[0035] As a further embodiment, in step S6, the glass phase content in the phase composition of the preform layer is 69.0%-88.5% by weight, and the chemical composition of the glass phase in the preform layer by weight includes: SiO2(A) 59.98%-67%, Al2O3 20.82%-27%, Fe2O3 0-2.64%, CaO 0.65%-5.85%, MgO 0.57%-6.49%, K2O 1.95%-6.26%, Na2O 0.5%-3.76%, TiO2 0-0.78%, the molar percentage of silicon dioxide SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is ≥27.0%, and the ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is ≥0.350.
[0036] As a further improvement, the fracture toughness of the low-crystalline silica content, environmentally friendly, and easily processed ceramic slab is ≥1.2 MPa·m. 1 / 2 The modulus of fracture is ≥50MPa.
[0037] Compared with the prior art, the beneficial effects of the present invention are: (1) This invention, through innovative design of the low-crystalline silica content ceramic slab body formulation system and efficient control of firing regime, produces a low-crystalline silica content environmentally friendly and easy-to-process ceramic slab body layer with a phase composition of crystalline silica SiO2 (C p The content of crystalline silica in the dust generated during the production of ceramic slabs is ≤10% by weight, which greatly reduces the content of crystalline silica in the dust generated during the production process of ceramic slabs and significantly reduces the content of crystalline silica in the phase composition of the green body layer of the produced ceramic slabs. This effectively reduces the risk of silicosis during the production and processing of ceramic slabs, and complies with the national call for green, healthy and environmentally friendly production. (2) This invention achieves efficient control through the linkage of the firing process of ceramic slabs with low crystalline silica content, which further reduces the amount of crystalline silica originally introduced by the raw materials during the firing process of the ceramic slab body. At the same time, it reduces the volume effect caused by the crystal transformation of crystalline silica during the cooling process of the ceramic slab, and reduces the residual stress in the body layer. The resulting ceramic slabs with low crystalline silica content have greater fracture toughness and fracture modulus. When processed according to the processability test method in T / CBCSA 40—2021 "Ceramic Slabs" standard, they achieve first-level processability, effectively reducing the high loss rate caused by cracking of the slabs in the later cold working.
[0038] (3) Before spray drying, the ceramic slab slurry is preheated by hot air and slurry gas / liquid heat exchanger in the cold section of the kiln tail, thereby reducing the energy consumption of the spray drying process, improving the energy utilization efficiency, increasing the production capacity, and achieving the purpose of energy saving and consumption reduction.
[0039] (4) Most of the raw materials used in the production of low-crystalline silica content ceramic slabs in this invention are the same as those used in conventional ceramic slab blanks. Only the process parameters need to be systematically adjusted on the basis of the existing ceramic slab production line. No other equipment needs to be added. The production process is economical and environmentally friendly, and the process is highly controllable. Detailed Implementation
[0040] To make the technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described more clearly and completely below with reference to specific embodiments. In the embodiments, unless otherwise specified, the equipment used is the same as that used in the production of conventional ceramic slabs. Example 1
[0041] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab body powder: The ceramic slab body slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab body powder for pressing ceramic slab bodies. The chemical composition of the ceramic slab body powder by dry weight percentage includes: SiO2 55.82%, Al2O3 26.15%, Fe2O3 1.62%, CaO 1.78%, MgO 2.81%, K2O 3.72%, Na2O 2.48%, loss on ignition 5.26%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The highest firing temperature is 1214℃, the firing cycle is 88.9min, and the holding time at the highest firing temperature is 25.0min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the surface of the body layer, denoted as T1. The phase composition of the body layer includes crystalline silicon dioxide SiO2 (C). p The content is 0% by weight.
[0042] In step S1, the raw materials for preparing the ceramic slab slurry are: ball clay A, washed clay A, raw talc B, calcined clay A, potassium sodium feldspar A, and potassium feldspar A.
[0043] In step S1, the ball milling system is a continuous ball milling system.
[0044] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0045] In step S1, a 100-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 3.14%, a specific gravity of 1.719 g / ml, and a flow rate of 26 s using an NK-2 Iwata viscosity cup.
[0046] In step S2, the moisture content of the ceramic slab blank powder is 6.8%, and the particle size is 51.4% residue on a 40-mesh sieve.
[0047] In step S3, the pressing pressure of the molding equipment is 37.5 MPa.
[0048] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 58.92%, Al2O3 27.60%, Fe2O3 1.71%, CaO 1.88%, MgO 2.97%, K2O 3.93%, Na2O 2.62%, with the balance being impurities.
[0049] In step S6, the content of the glass phase in the phase composition of the green body layer is 88.50% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 63.03%, Al2O3 22.10%, Fe2O3 1.57%, CaO 2.12%, MgO 3.36%, K2O 4.44%, Na2O 2.96%, TiO2 0.42%. The molar percentage of silica SiO2(E) in the glass phase of the green body layer exceeding the stoichiometry provided by feldspar is 27.1%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the green body layer is 0.562. Example 2
[0050] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab blank powder: The ceramic slab blank slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab blank powder for pressing ceramic slab blanks. The chemical composition of the ceramic slab blank powder by dry weight percentage includes: SiO2 57.27%, Al2O3 25.93%, Fe2O3 1.63%, CaO 0.83%, MgO 1.85%, K2O 3.68%, Na2O 2.48%, loss on ignition 5.98%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The maximum firing temperature is 1250℃, the firing cycle is 55.0 min, and the holding time at the maximum firing temperature is 23.7 min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the surface of the body layer, denoted as T2. The phase composition of the body layer includes crystalline silicon dioxide (SiO2, C2O2). p The content by weight percentage is 2.0%.
[0051] In step S1, the raw materials for preparing the ceramic slab slurry are: ball clay A, washed clay A, raw talc B, calcined clay A, potassium sodium feldspar A, and potassium feldspar A.
[0052] In step S1, the ball milling system is an intermittent ball milling system.
[0053] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0054] In step S1, an 80-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 3.50%, a specific gravity of 1.740 g / ml, and a flow rate of 32 s using an NK-2 Iwata viscosity cup.
[0055] In step S2, the moisture content of the ceramic slab blank powder is 7.5%, and the particle size is 55.0% residue on a 40-mesh sieve.
[0056] In step S3, the pressing pressure of the molding equipment is 35.0 MPa.
[0057] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 60.92%, Al2O3 27.57%, Fe2O3 1.73%, CaO 0.88%, MgO 1.97%, K2O 3.91%, Na2O 2.64%, with the balance being impurities.
[0058] In step S6, the glass phase content in the phase composition of the green body layer is 88.00% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 63.87%, Al2O3 23.42%, Fe2O3 1.60%, CaO 1.00%, MgO 2.24%, K2O 4.44%, Na2O 3.00%, TiO2 0.43%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 30.8%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.436. Example 3
[0059] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab blank powder: The ceramic slab blank slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab blank powder for pressing ceramic slab blanks. The chemical composition of the ceramic slab blank powder by dry weight percentage includes: SiO2 60.52%, Al2O3 20.50%, Fe2O3 0%, CaO 6.52%, MgO 0.47%, K2O 1.95%, Na2O 2.80%, loss on ignition 6.82%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The highest firing temperature is 1179℃, the firing cycle is 122.9min, and the holding time at the highest firing temperature is 22.4min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the surface of the body layer, denoted as T3. The phase composition of the body layer includes crystalline silicon dioxide SiO2 (C). p The content by weight percentage is 3.0%.
[0060] In step S1, the raw materials for preparing the ceramic slab slurry are: raw talc B, ball clay B, TM2106 frit, kaolin B, and calcined clay B.
[0061] In step S1, the ball milling system is a continuous ball milling system.
[0062] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0063] In step S1, a 120-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 2.79%, a specific gravity of 1.697 g / ml, and a flow rate of NK-2 Iwata viscosity cup 21s.
[0064] In step S2, the moisture content of the ceramic slab blank powder is 6.1%, and the particle size is 47.9% residue on a 40-mesh sieve.
[0065] In step S3, the pressing pressure of the molding equipment is 40.0 MPa.
[0066] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 64.95%, Al2O3 22.00%, Fe2O3 30%, CaO 7.00%, MgO 0.50%, K2O 2.09%, Na2O 3.00%, with the balance being impurities.
[0067] In step S6, the content of the glass phase in the phase composition of the green body layer is 87.00% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 66.33%, Al2O3 20.87%, Fe2O3 0%, CaO 5.85%, MgO 0.57%, K2O 2.40%, Na2O 3.45%, TiO2 0.53%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 27.0%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.594. Example 4
[0068] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab body powder: The ceramic slab body slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab body powder for pressing ceramic slab bodies. The chemical composition of the ceramic slab body powder by dry weight percentage includes: SiO2 56.17%, Al2O3 26.91%, Fe2O3 2.70%, CaO 2.68%, MgO 0.82%, K2O 3.40%, Na2O 2.18%, loss on ignition 4.90%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The highest firing temperature is 1243℃, the firing cycle is 61.8min, and the holding time at the highest firing temperature is 21.1min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the surface of the body layer, denoted as T4. The phase composition of the body layer includes crystalline silicon dioxide SiO2 (C). p The content by weight percentage is 4.0%.
[0069] In step S1, the raw materials for preparing the ceramic slab slurry are: washed clay A, raw talc A, calcined bauxite B, potassium sodium feldspar A, potassium feldspar A, and kaolin A.
[0070] In step S1, the ball milling system is an intermittent ball milling system.
[0071] In step S2, before spray drying the ceramic slab slurry obtained in step S1, the ceramic slab slurry is subjected to slurry preheating treatment.
[0072] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0073] In step S1, an 80-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 3.43%, a specific gravity of 1.736 g / ml, and a flow rate of 31 s using an NK-2 Iwata viscosity cup.
[0074] In step S2, the moisture content of the ceramic slab blank powder is 7.4%, and the particle size is 54.3% residue on a 40-mesh sieve.
[0075] In step S3, the pressing pressure of the molding equipment is 35.5 MPa.
[0076] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 59.06%, Al2O3 28.30%, Fe2O3 2.84%, CaO 2.82%, MgO 0.86%, K2O 3.57%, Na2O 2.29%, with the balance being impurities.
[0077] In step S6, the content of the glass phase in the phase composition of the green body layer is 86.23% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 60.00%, Al2O3 27.00%, Fe2O3 2.50%, CaO 2.41%, MgO 1.00%, K2O 4.14%, Na2O 2.66%, TiO2 0.30%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 27.3%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.439. Example 5
[0078] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab blank powder: The ceramic slab blank slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab blank powder for pressing ceramic slab blanks. The chemical composition of the ceramic slab blank powder by dry weight percentage includes: SiO2 58.89%, Al2O3 25.11%, Fe2O3 1.89%, CaO 1.72%, MgO 0.97%, K2O 4.27%, Na2O 2.24%, loss on ignition 4.72%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The highest firing temperature is 1236℃, the firing cycle is 68.6min, and the holding time at the highest firing temperature is 19.9min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the surface of the body layer, denoted as T5. The phase composition of the body layer includes crystalline silicon dioxide SiO2 (C). p The content is 4.5% by weight.
[0079] In step S1, the raw materials for preparing the ceramic slab slurry are: ball clay A, washed clay A, washed clay B, wollastonite A, potassium sodium feldspar B, raw talc A, potassium feldspar B, calcined bauxite B, and diopside.
[0080] In step S1, the ball milling system is a continuous ball milling system.
[0081] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0082] In step S1, an 80-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 3.36%, a specific gravity of 1.731 g / ml, and a flow rate of 30 s using an NK-2 Iwata viscosity cup.
[0083] In step S2, the moisture content of the ceramic slab blank powder is 7.2%, and the particle size is 53.6% residue on a 40-mesh sieve.
[0084] In step S3, the pressing pressure of the molding equipment is 36.0 MPa.
[0085] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 61.81%, Al2O3 26.36%, Fe2O3 1.98%, CaO 1.80%, MgO 1.02%, K2O 4.48%, Na2O 2.35%, with the balance being impurities.
[0086] In step S6, the glass phase content in the phase composition of the green body layer is 85.57% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 63.25%, Al2O3 24.05%, Fe2O3 1.94%, CaO 1.36%, MgO 1.19%, K2O 5.24%, Na2O 2.75%, TiO2 0.23%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 27.8%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.350. Example 6
[0087] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab body powder: The ceramic slab body slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab body powder for pressing ceramic slab bodies. The chemical composition of the ceramic slab body powder by dry weight percentage includes: SiO2 60.49%, Al2O3 21.77%, Fe2O3 0.26%, CaO 4.85%, MgO 2.49%, K2O 3.01%, Na2O 1.10%, loss on ignition 5.87%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The highest firing temperature is 1186℃, the firing cycle is 116.1min, and the holding time at the highest firing temperature is 18.6min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the surface of the body layer, denoted as T6. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p The content is 6.5% by weight.
[0088] In step S1, the raw materials for preparing the ceramic slab slurry are: wollastonite A, raw talc B, potassium feldspar B, ball clay B, pyrophyllite, kaolin B, and calcined clay B.
[0089] In step S1, the ball milling system is an intermittent ball milling system.
[0090] In step S2, before spray drying the ceramic slab slurry obtained in step S1, the ceramic slab slurry is subjected to slurry preheating treatment.
[0091] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0092] In step S1, a 120-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 2.86%, a specific gravity of 1.701 g / ml, and a flow rate of NK-2 Iwata viscosity cup 22s.
[0093] In step S2, the moisture content of the ceramic slab blank powder is 6.2%, and the particle size is 48.6% residue on a 40-mesh sieve.
[0094] In step S3, the pressing pressure of the molding equipment is 39.5 MPa.
[0095] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 64.19%, Al2O3 23.59%, Fe2O3 0.30%, CaO 4.88%, MgO 2.68%, K2O 3.14%, Na2O 1.02%, with the balance being impurities.
[0096] In step S6, the glass phase content in the phase composition of the green body layer is 79.41% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 65.53%, Al2O3 21.67%, Fe2O3 0.38%, CaO 3.73%, MgO 3.19%, K2O 3.95%, Na2O 1.28%, and TiO2 0.26%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 38.3%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.700. Example 7
[0097] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab blank powder: The ceramic slab blank slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab blank powder for pressing ceramic slab blanks. The chemical composition of the ceramic slab blank powder by dry weight percentage includes: SiO2 59.91%, Al2O3 23.12%, Fe2O3 0%, CaO 4.69%, MgO 1.96%, K2O 4.51%, Na2O 1.16%, loss on ignition 4.65%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The maximum firing temperature is 1150℃, the firing cycle is 150.0 min, and the holding time at the maximum firing temperature is 17.3 min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the surface of the body layer, denoted as T7. The phase composition of the body layer includes crystalline silicon dioxide (SiO2, C). p The content by weight percentage is 6.7%.
[0098] In step S1, the raw materials for preparing the ceramic slab blank slurry are: rock mud, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina B, and potassium feldspar A.
[0099] In step S1, the ball milling system is a continuous ball milling system.
[0100] In step S2, before spray drying the ceramic slab slurry obtained in step S1, the ceramic slab slurry is subjected to slurry preheating treatment.
[0101] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0102] In step S1, a 150-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 2.50%, a specific gravity of 1.680 g / ml, and a flow rate of 16 s using an NK-2 Iwata viscosity cup.
[0103] In step S2, the moisture content of the ceramic slab blank powder is 5.5%, and the particle size is 45.0% residue on a 40-mesh sieve.
[0104] In step S3, the pressing pressure of the molding equipment is 42.0 MPa.
[0105] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 62.83%, Al2O3 24.25%, Fe2O3 30%, CaO 4.92%, MgO 2.06%, K2O 4.73%, Na2O 1.21%, with the balance being impurities.
[0106] In step S6, the glass phase content in the phase composition of the green body layer is 78.80% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 65.18%, Al2O3 21.00%, Fe2O3 0%, CaO 4.08%, MgO 2.21%, K2O 6.00%, Na2O 1.54%, TiO2 0%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 27.1%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.591. Example 8
[0107] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab body powder: The ceramic slab body slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab body powder for pressing ceramic slab bodies. The chemical composition of the ceramic slab body powder by dry weight percentage includes: SiO2 58.74%, Al2O3 23.70%, Fe2O3 0.26%, CaO 4.77%, MgO 2.45%, K2O 3.44%, Na2O 1.34%, loss on ignition 5.13%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The highest firing temperature is 1171℃, the firing cycle is 129.6min, and the holding time at the highest firing temperature is 16.0min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the surface of the body layer, denoted as T8. The phase composition of the body layer includes crystalline silicon dioxide (SiO2, C). p The content is 7.0% by weight.
[0108] In step S1, the raw materials for preparing the ceramic slab slurry are: rock mud, wollastonite A, raw talc B, potassium feldspar B, pyrophyllite, kaolin B, calcined clay B, potassium feldspar A, and calcined bauxite B.
[0109] In step S1, the ball milling system is an intermittent ball milling system.
[0110] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0111] In step S1, a 150-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 2.71%, a specific gravity of 1.693 g / ml, and a flow rate of 19 s using an NK-2 Iwata viscosity cup.
[0112] In step S2, the moisture content of the ceramic slab blank powder is 5.9%, and the particle size is 47.1% residue on a 40-mesh sieve.
[0113] In step S3, the pressing pressure of the molding equipment is 40.5 MPa.
[0114] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 62.05%, Al2O3 25.01%, Fe2O3 0.25%, CaO 5.08%, MgO 2.62%, K2O 3.46%, Na2O 1.32%, with the balance being impurities.
[0115] In step S6, the content of the glass phase in the phase composition of the green body layer is 78.11% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 63.00%, Al2O3 23.52%, Fe2O3 0.32%, CaO 3.92%, MgO 2.84%, K2O 4.43%, Na2O 1.69%, and TiO2 0.28%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 30.9%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.655. Example 9
[0116] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab body powder: The ceramic slab body slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab body powder for pressing ceramic slab bodies. The chemical composition of the ceramic slab body powder by dry weight percentage includes: SiO2 60.56%, Al2O3 22.69%, Fe2O3 0.27%, CaO 4.23%, MgO 2.34%, K2O 4.80%, Na2O 0.85%, loss on ignition 4.01%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The highest firing temperature is 1164℃, the firing cycle is 136.4min, and the holding time at the highest firing temperature is 14.7min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the surface of the body layer, denoted as T9. The phase composition of the body layer includes crystalline silicon dioxide SiO2 (C). p The content by weight percentage is 7.2%.
[0117] In step S1, the raw materials for preparing the ceramic slab slurry are: raw talc B, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina A, and kaolin B.
[0118] In step S1, the ball milling system is a continuous ball milling system.
[0119] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0120] In step S1, a 150-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 2.64%, a specific gravity of 1.689 g / ml, and a flow rate of 18 s using an NK-2 Iwata viscosity cup.
[0121] In step S2, the moisture content of the ceramic slab blank powder is 5.8%, and the particle size is 46.4% residue on a 40-mesh sieve.
[0122] In step S3, the pressing pressure of the molding equipment is 41.0 MPa.
[0123] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 63.09%, Al2O3 23.64%, Fe2O3 0.28%, CaO 4.41%, MgO 2.44%, K2O 5.00%, Na2O 0.89%, with the balance being impurities.
[0124] In step S6, the content of the glass phase in the phase composition of the green body layer is 77.91% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 64.10%, Al2O3 20.82%, Fe2O3 0.35%, CaO 4.16%, MgO 2.88%, K2O 6.26%, Na2O 1.11%, TiO2 0.31%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 27.3%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.634. Example 10
[0125] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab body powder: The ceramic slab body slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab body powder for pressing ceramic slab bodies. The chemical composition of the ceramic slab body powder by dry weight percentage includes: SiO2 57.66%, Al2O3 23.26%, Fe2O3 0.23%, CaO 4.58%, MgO 2.53%, K2O 3.06%, Na2O 1.18%, loss on ignition 6.48%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The highest firing temperature is 1193℃, the firing cycle is 109.3min, and the holding time at the highest firing temperature is 13.4min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the upper surface of the body layer, denoted as T10. The phase composition of the body layer contains crystalline silicon dioxide SiO2 (C p The content by weight percentage is 7.3%.
[0126] In step S1, the raw materials for preparing the ceramic slab slurry are: raw talc B, wollastonite B, potassium feldspar B, ball clay B, pyrophyllite, kaolin B, bone ash, and calcined bauxite A.
[0127] In step S1, the ball milling system is an intermittent ball milling system.
[0128] In step S2, before spray drying the ceramic slab slurry obtained in step S1, the ceramic slab slurry is subjected to slurry preheating treatment.
[0129] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0130] In step S1, a 120-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 2.93%, a specific gravity of 1.706 g / ml, and a flow rate of NK-2 Iwata viscosity cup 23s.
[0131] In step S2, the moisture content of the ceramic slab blank powder is 6.4%, and the particle size is 49.3% residue on a 40-mesh sieve.
[0132] In step S3, the pressing pressure of the molding equipment is 39.0 MPa.
[0133] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 62.16%, Al2O3 24.95%, Fe2O3 0.40%, CaO 4.73%, MgO 2.97%, K2O 3.29%, Na2O 1.17%, with the balance being impurities.
[0134] In step S6, the glass phase content in the phase composition of the green body layer is 77.51% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 63.09%, Al2O3 23.12%, Fe2O3 0.51%, CaO 3.45%, MgO 3.65%, K2O 4.25%, Na2O 1.51%, TiO2 0.41%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 33.9%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.687. Example 11
[0135] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab body powder: The ceramic slab body slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab body powder for pressing ceramic slab bodies. The chemical composition of the ceramic slab body powder by dry weight percentage includes: SiO2 60.28%, Al2O3 21.69%, Fe2O3 0.19%, CaO 4.89%, MgO 1.65%, K2O 3.79%, Na2O 1.07%, loss on ignition 5.59%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The highest firing temperature is 1207℃, the firing cycle is 95.7min, and the holding time at the highest firing temperature is 12.1min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the surface of the body layer, denoted as T11. The phase composition of the body layer includes crystalline silicon dioxide SiO2 (C). p The content is 7.5% by weight.
[0136] In step S1, the raw materials for preparing the ceramic slab slurry are: raw talc B, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina B, kaolin B, and bone ash.
[0137] In step S1, the ball milling system is a continuous ball milling system.
[0138] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0139] In step S1, a 100-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 3.07%, a specific gravity of 1.714 g / ml, and a flow rate of 25 s using an NK-2 Iwata viscosity cup.
[0140] In step S2, the moisture content of the ceramic slab blank powder is 6.6%, and the particle size is 50.7% residue on a 40-mesh sieve.
[0141] In step S3, the pressing pressure of the molding equipment is 38.0 MPa.
[0142] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 63.91%, Al2O3 23.50%, Fe2O3 0.32%, CaO 4.78%, MgO 1.97%, K2O 4.03%, Na2O 1.37%, with the balance being impurities.
[0143] In step S6, the glass phase content in the phase composition of the green body layer is 77.31% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 65.40%, Al2O3 21.77%, Fe2O3 0.41%, CaO 3.08%, MgO 2.19%, K2O 5.22%, Na2O 1.77%, TiO2 0.16%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 31.7%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.566. Example 12
[0144] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab body powder: The ceramic slab body slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab body powder for pressing ceramic slab bodies. The chemical composition of the ceramic slab body powder by dry weight percentage includes: SiO2 55.68%, Al2O3 27.36%, Fe2O3 2.88%, CaO 0.48%, MgO 4.80%, K2O 1.44%, Na2O 2.78%, loss on ignition 4.00%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The highest firing temperature is 1229℃, the firing cycle is 75.4min, and the holding time at the highest firing temperature is 10.9min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the surface of the body layer, denoted as T12. The phase composition of the body layer includes crystalline silicon dioxide SiO2 (C). p The content by weight percentage is 7.8%.
[0145] In step S1, the raw materials for preparing the ceramic slab slurry are: ball clay A, washed clay A, washed clay B, wollastonite A, potassium sodium feldspar B, raw talc A, potassium feldspar B, and calcined bauxite B.
[0146] In step S1, the ball milling system is an intermittent ball milling system.
[0147] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0148] In step S1, an 80-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 3.29%, a specific gravity of 1.727 g / ml, and a flow rate of 29 s using an NK-2 Iwata viscosity cup.
[0149] In step S2, the moisture content of the ceramic slab blank powder is 7.1%, and the particle size is 52.9% residue on a 40-mesh sieve.
[0150] In step S3, the pressing pressure of the molding equipment is 36.5 MPa.
[0151] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 58.00%, Al2O3 28.50%, Fe2O3 3.00%, CaO 0.50%, MgO 5.00%, K2O 1.50%, Na2O 2.90%, with the balance being impurities.
[0152] In step S6, the glass phase content in the phase composition of the green body layer is 77.07% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 59.98%, Al2O3 23.75%, Fe2O3 2.64%, CaO 0.65%, MgO 6.49%, K2O 1.95%, Na2O 3.76%, TiO2 0.78%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 32.2%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.681. Example 13
[0153] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab blank powder: The ceramic slab blank slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab blank powder for pressing ceramic slab blanks. The chemical composition of the ceramic slab blank powder by dry weight percentage includes: SiO2 62.00%, Al2O3 22.38%, Fe2O3 0.05%, CaO 4.04%, MgO 1.81%, K2O 3.85%, Na2O 1.12%, loss on ignition 4.62%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The highest firing temperature is 1221℃, the firing cycle is 82.1min, and the holding time at the highest firing temperature is 9.6min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the upper surface of the body layer, denoted as T13. The phase composition of the body layer includes crystalline silicon dioxide SiO2 (C). p The content by weight percentage is 8.0%.
[0154] In step S1, the raw materials for preparing the ceramic slab slurry are: raw talc B, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina B, kaolin B, and fused silica.
[0155] In step S1, the ball milling system is a continuous ball milling system.
[0156] In step S2, before spray drying the ceramic slab slurry obtained in step S1, the ceramic slab slurry is subjected to slurry preheating treatment.
[0157] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0158] In step S1, a 100-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 3.21%, a specific gravity of 1.723 g / ml, and a flow rate of 27 s using an NK-2 Iwata viscosity cup.
[0159] In step S2, the moisture content of the ceramic slab blank powder is 6.9%, and the particle size is 52.1% residue on a 40-mesh sieve.
[0160] In step S3, the pressing pressure of the molding equipment is 37.0 MPa.
[0161] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 65.00%, Al2O3 23.46%, Fe2O3 0.05%, CaO 4.24%, MgO 1.90%, K2O 4.04%, Na2O 1.17%, with the balance being impurities.
[0162] In step S6, the content of the glass phase in the phase composition of the green body layer is 76.91% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 67.00%, Al2O3 21.51%, Fe2O3 0.06%, CaO 2.53%, MgO 1.95%, K2O 5.26%, Na2O 1.52%, TiO2 0.18%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 36.2%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.539. Example 14
[0163] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab body powder: The ceramic slab body slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab body powder for pressing ceramic slab bodies. The chemical composition of the ceramic slab body powder by dry weight percentage includes: SiO2 57.98%, Al2O3 22.63%, Fe2O3 0.12%, CaO 6.10%, MgO 3.82%, K2O 1.63%, Na2O 0.33%, loss on ignition 7.00%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The highest firing temperature is 1157℃, the firing cycle is 143.2min, and the holding time at the highest firing temperature is 8.3min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the surface of the body layer, denoted as T14. The phase composition of the body layer includes crystalline silicon dioxide SiO2 (C). p The content is 8.5% by weight.
[0164] In step S1, the raw materials for preparing the ceramic slab slurry are: raw talc B, ball clay B, TM2106 frit, kaolin B, and calcined clay B.
[0165] In step S1, the ball milling system is an intermittent ball milling system.
[0166] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0167] In step S1, a 150-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 2.57%, a specific gravity of 1.684 g / ml, and a flow rate of 17 s using an NK-2 Iwata viscosity cup.
[0168] In step S2, the moisture content of the ceramic slab blank powder is 5.6%, and the particle size is 45.7% residue on a 40-mesh sieve.
[0169] In step S3, the pressing pressure of the molding equipment is 41.5 MPa.
[0170] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 62.34%, Al2O3 24.33%, Fe2O3 0.13%, CaO 6.56%, MgO 4.11%, K2O 1.75%, Na2O 0.35%, with the balance being impurities.
[0171] In step S6, the content of the glass phase in the phase composition of the green body layer is 70.00% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 63.88%, Al2O3 21.84%, Fe2O3 0.19%, CaO 5.50%, MgO 5.00%, K2O 2.50%, Na2O 0.50%, TiO2 0.60%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 42.7%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.866. Example 15
[0172] S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab body powder: The ceramic slab body slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab body powder for pressing ceramic slab bodies. The chemical composition of the ceramic slab body powder by dry weight percentage includes: SiO2 60.11%, Al2O3 22.30%, Fe2O3 0.19%, CaO 5.45%, MgO 4.09%, K2O 1.46%, Na2O 0.40%, loss on ignition 5.82%, and the balance being impurities; S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blanks: The decorated ceramic slab blanks obtained in step S4 are fired at high temperature to obtain ceramic slab semi-finished products. The maximum firing temperature is 1200℃, the firing cycle is 102.5min, and the holding time at the maximum firing temperature is 7.0min. S6, Post-processing of semi-finished ceramic slabs: Post-processing of semi-finished ceramic slabs yields finished ceramic slabs containing a body layer and a decorative layer on the surface of the body layer, denoted as T15. The phase composition of the body layer includes crystalline silicon dioxide SiO2 (C). p The content by weight percentage is 10.0%.
[0173] In step S1, the raw materials for preparing the ceramic slab slurry are: raw talc B, potassium feldspar B, ball clay B, pyrophyllite, TM2106 frit, calcined alumina B, kaolin B, and bone ash.
[0174] In step S1, the ball milling system is a continuous ball milling system.
[0175] In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
[0176] In step S1, a 120-mesh vibrating screen is used for sieving. The fineness of the ceramic slab slurry is 325 mesh with a residue of 3.00%, a specific gravity of 1.710 g / ml, and a flow rate of 24 s using an NK-2 Iwata viscosity cup.
[0177] In step S2, the moisture content of the ceramic slab blank powder is 6.5%, and the particle size is 50.0% residue on a 40-mesh sieve.
[0178] In step S3, the pressing pressure of the molding equipment is 38.5 MPa.
[0179] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 63.83%, Al2O3 23.68%, Fe2O3 0.20%, CaO 5.79%, MgO 4.34%, K2O 1.55%, Na2O 0.42%, with the balance being impurities.
[0180] In step S6, the glass phase content in the phase composition of the green body layer is 69.00% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 64.93%, Al2O3 21.74%, Fe2O3 0.29%, CaO 4.57%, MgO 5.33%, K2O 2.25%, Na2O 0.61%, TiO2 0.28%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 46.3%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.864. Comparative Example Comparative Example 1
[0181] Similar to Example 15, except that the raw material ratio for preparing the ceramic slab blank slurry is different, denoted as D1. In step S2, the chemical composition of the ceramic slab blank powder, by dry weight percentage, includes: SiO2 63.97%, Al2O3 23.55%, Fe2O3 0.39%, CaO 0.47%, MgO 0.11%, K2O 1.39%, Na2O 5.53%, loss on ignition 4.30%, and the balance being impurities.
[0182] In step S6, the phase composition of the preform layer includes crystalline silicon dioxide (SiO2) (C p The content by weight percentage is 10.1%.
[0183] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 66.84%, Al2O3 24.61%, Fe2O3 0.41%, CaO 0.49%, MgO 0.11%, K2O 1.45%, Na2O 5.78%, with the balance being impurities.
[0184] In step S6, the content of the glass phase in the phase composition of the green body layer by weight percentage is 68.53%, and the chemical composition of the glass phase in the phase composition of the green body layer by weight percentage includes: SiO2(A) 69.00%, Al2O3 20.09%, Fe2O3 0.60%, CaO 0.57%, MgO 0.16%, K2O 2.12%, Na2O 7.01%, TiO2 0.45%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 21.0%, and the ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.095. Comparative Example 2
[0185] Similar to Example 5, except that the raw material ratio for preparing the ceramic slab blank slurry is different, denoted as D2. In step S2, the chemical composition of the ceramic slab blank powder, by dry weight percentage, includes: SiO2 65.73%, Al2O3 19.55%, Fe2O3 0.33%, CaO 1.52%, MgO 0.48%, K2O 2.88%, Na2O 2.78%, loss on ignition 6.46%, and the balance being impurities.
[0186] In step S6, the phase composition of the preform layer includes crystalline silicon dioxide (SiO2) (C p The content by weight percentage is 21.7%.
[0187] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 70.27%, Al2O3 20.91%, Fe2O3 0.35%, CaO 1.63%, MgO 0.51%, K2O 3.08%, Na2O 2.97%, with the balance being impurities.
[0188] In step S6, the glass phase content in the phase composition of the green body layer is 65.60% by weight, and the chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 67.76%, Al2O3 19.13%, Fe2O3 0.53%, CaO 2.35%, MgO 0.78%, K2O 4.69%, Na2O 4.32%, TiO2 0.43%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 21.8%, and the ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.340. Comparative Example 3
[0189] Similar to Example 3, except that the raw material ratio for preparing the ceramic slab blank slurry is different, denoted as D3. In step S2, the chemical composition of the ceramic slab blank powder, by dry weight percentage, includes: SiO2 67.82%, Al2O3 20.59%, Fe2O3 0.20%, CaO 0.33%, MgO 0.22%, K2O 4.82%, Na2O 0.87%, loss on ignition 4.79%, and the balance being impurities.
[0190] In step S6, the phase composition of the preform layer includes crystalline silicon dioxide (SiO2) (C p The content by weight percentage is 28.6%.
[0191] The chemical composition of the green body layer by weight percentage includes: SiO2(T) 71.23%, Al2O3 21.62%, Fe2O3 0.21%, CaO 0.34%, MgO 0.23%, K2O 5.06%, Na2O 0.91%, with the balance being impurities.
[0192] In step S6, the content of the glass phase in the phase composition of the green body layer by weight percentage is 58.70%, and the chemical composition of the glass phase in the phase composition of the green body layer by weight percentage includes: SiO2(A) 66.47%, Al2O3 21.38%, Fe2O3 0.35%, CaO 0.58%, MgO 0.40%, K2O 8.62%, Na2O 1.53%, TiO2 0.67%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 26.5%, and the ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.149. Comparative Example 4
[0193] Same as Example 15, except that the holding time at the highest firing temperature is 6.0 min, denoted as D4. In step S6, the phase composition of the green body layer is crystalline silicon dioxide SiO2 (C p The content by weight percentage is 12.0%.
[0194] In step S6, the content of the glass phase in the phase composition of the green body layer is 67.02% by weight. The chemical composition of the glass phase in the phase composition of the green body layer by weight includes: SiO2(A) 63.90%, Al2O3 22.34%, Fe2O3 0.30%, CaO 4.77%, MgO 5.47%, K2O 2.31%, Na2O 0.63%, TiO2 0.28%. The molar percentage of silica SiO2(E) in the glass phase of the phase composition of the green body layer exceeding the stoichiometry provided by feldspar is 44.4%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the phase composition of the green body layer is 0.865.
[0195] Performance Test Examples
[0196] Performance Test Example 1
[0197] The ceramic slabs prepared in Examples 1-15 (T1-T15) and Comparative Examples 1-4 (D1-D4) were subjected to the following performance tests according to the following standards, and the results are shown in Table 1 below.
[0198] Table 1. Performance test results of ceramic slabs <![CDATA[SiO2(C p )(wt %)]]> 0.0 2.0 3.0 4.0 4.5 6.5 6.7 7.0 7.2 7.3 7.5 7.8 8.0 8.5 10.0 10.1 21.7 28.6 12.0 <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> 2.00 1.94 1.89 1.83 1.77 1.71 1.66 1.60 1.54 1.49 1.43 1.37 1.31 1.26 1.20 1.18 0.94 0.79 1.12 Modulus of fracture (MPa) 100.0 96.4 92.9 89.3 85.7 82.1 78.6 75.0 71.4 67.9 64.3 60.7 57.1 53.6 50.0 48.2 39.5 37.2 45.7 Machinability Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 1 Level 2 Level 3 Level 3 Level 2 Fracture toughness: Tested using the indentation method, the specific procedure is as follows: The test specimen surface was first polished to a mirror finish. Then, using a microhardness tester, a 10 kg load was applied to the polished surface using the conical diamond indenter of the hardness tester to create an indentation. This resulted in pre-existing cracks at the four vertices of the indentation. The fracture toughness (K) value was calculated based on the indentation load P and the indentation crack propagation length C. IC The calculation formula is:
[0199] Among them, Young's modulus E is in GPa, load P is in N, crack length C is in mm, and microhardness H is... V The unit is GPa.
[0200] Modulus of rupture: The modulus of rupture was determined in accordance with GB / T 3810.4-2016 "Test methods for ceramic tiles - Part 4: Determination of modulus of rupture and breaking strength".
[0201] Machinability: Machinability test method in T / CBCSA 40—2021 "Ceramic Slab" standard is used.
[0202] In this application, the phase composition of the green body layer of the ceramic slab includes crystalline silicon dioxide (SiO2) (C... p The most direct way to determine whether ceramic slabs are environmentally friendly is by measuring the content as a percentage by weight. As can be seen from the table above, the crystalline silicon dioxide (SiO2) content of ceramic slabs T1-T15 produced in Examples 1-15 is... p The content of silica (SiO2) in ceramic slabs (T1-T15) is 10% or less by weight. Therefore, it does not generate much respirable dust with high silica content during either the initial raw material processing of ceramic slabs or the subsequent cutting and polishing processes. This effectively reduces the risk of silicosis during the production and processing of ceramic slabs. Furthermore, because the silica content of ceramic slabs T1-T15 is relatively low, the silica content is significantly reduced. p The content of silica (SiO2) in ceramic slabs is relatively low by weight percentage. The stress caused by the crystal transformation of silica in the ceramic slabs is also smaller, resulting in first-class machinability and less loss due to cold working cracking. However, the ceramic slabs D1-D4 produced in Comparative Examples 1-4, although produced according to the process conditions of Examples 15, 5, 3, and 15 respectively, exhibit different proportions of raw materials used in the ceramic slab slurry preparations compared to Examples T15, T5, and T3, and different holding times at the highest firing temperature compared to T15. This leads to a difference in the content of crystalline silica (SiO2) in ceramic slabs D1-D4. pThe content of these substances, by weight percentage, is all higher than 10%, which increases the risk of silicosis during the production and processing of ceramic slabs. Secondly, the presence of crystalline silicon dioxide (SiO2) in the body layers of ceramic slabs D1-D4 further contributes to this risk. p The high silica content (by weight percentage) results in significant stress due to the crystal transformation of silica in the ceramic slabs, leading to poor machinability and substantial losses due to cold working cracking. These data objectively reflect the significant improvements in environmental protection and processing performance of the ceramic slabs produced in this application. In particular, the ceramic slabs produced in Example 1 do not generate respirable dust with high silica content during cutting and grinding, resulting in a very low risk of silicosis. Furthermore, they exhibit good toughness, high strength, and excellent machinability.
[0203] Fracture toughness and fracture modulus are the most important data determining the high toughness, high strength, and machinability of ceramic slabs. As shown in the table above, the fracture toughness of ceramic slabs T1-T15 produced in Examples 1-15 is all above 1.20 MPa·m. 1 / 2 The fracture modulus of all samples were 50 MPa or higher, and the machinability was Grade 1. However, Comparative Example 1, produced under the process conditions of Example 15, differed from T15 in the raw material ratio of the ceramic slab slurry. The glass phase content in the green body layer was 68.53% by weight, lower than 69.00%, indicating a relatively low glass phase content. This insufficient glass phase to bind the crystalline phase resulted in lower interphase bonding, leading to a fracture toughness of less than 1.20 MPa·m for D1. 1 / 2 First, the fracture modulus is less than 50 MPa; second, the corresponding crystalline silicon dioxide SiO2 (C p The content of the silica by weight percentage is higher than 10%. During the firing process, the crystalline silica undergoes a crystal transformation, generating significant stress, resulting in a workability level of only two. Comparative Examples 2 and 3 were produced according to the process conditions of Examples 5 and 3, respectively. The difference between D2 and D3 and T5 and T3 is that the raw materials used to prepare the ceramic slab green body slurry are the same but the proportions are different. In the phase composition of the green body layer of D2, the ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase is 0.340, which is lower than the value of D2. In the D3 green body layer, the percentage of silica (SiO2(E)) in the glassy phase exceeding the stoichiometric amount provided by feldspar is 26.5% and lower than 27.0%. Correspondingly, the ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glassy phase of the D3 green body layer is 0.149 and lower than 0.350. This results in insufficient solubility of the glassy phase in the green body layer during ceramic slab firing, leading to a small amount of crystalline silica (SiO2(E)) introduced from the raw materials.r The ability of D2 and D3 crystalline silicon dioxide (SiO2(C)) to transform into amorphous silicon dioxide and silicon dioxide existing as a component in other crystalline phases besides crystalline silicon dioxide is poor. p The content of ) by weight percentage is relatively high, and the corresponding processability grade is low, only level three; Comparative Example 4, D4 produced according to the process conditions of Example 15, differs from T15 in that the holding time at the highest firing temperature is 6 min, less than 7 min. Due to the insufficient holding time at the highest firing temperature, on the one hand, a small amount of crystalline silicon dioxide SiO2 (C) brought in from the raw material is lost. r There is insufficient time for the silica to transform into the glassy phase and other crystalline phases besides crystalline silica, which are present as components. Furthermore, this hinders the oxidative decomposition of humic substances in the ceramic slab body, leading to a decrease in the density of the body layer. Therefore, the fracture toughness and fracture modulus of D4 are lower than T15, and its machinability only reaches level two. This fully demonstrates the feasibility of the proposed method for improving the machinability of ceramic slabs and its significant advantages in machinability performance.
[0204] Based on the disclosure and guidance provided in the foregoing specification, those skilled in the art can make changes and modifications to the above embodiments. Therefore, this application is not limited to the specific embodiments disclosed and described above, and any modifications and alterations should fall within the scope of protection of the claims of this application. Furthermore, although this specification uses certain specific terms, these terms are merely for convenience and do not constitute any limitation on this application.
Claims
1. A low-crystalline silica content, environmentally friendly, and easily processed ceramic slab, characterized in that: It includes a blank layer and a decorative layer disposed on the upper surface of the blank layer, wherein the phase composition of the blank layer is crystalline silicon dioxide SiO2 (C p The content, expressed as a percentage by weight, is ≤10%; The chemical composition of the blank layer by weight percentage includes: SiO2(T) 58%-65%, Al2O3 22%-28.5%, Fe2O3 0-3%, CaO 0.5%-7%, MgO 0.5%-5%, K2O 1.5%-5%, Na2O 0.35%-3%, with the balance being impurities; The phase composition of the green body layer, in terms of weight percentage, includes the following chemical composition of the glass phase: SiO2(A) 59.98%-67%, Al2O3 20.82%-27%, Fe2O3 0-2.64%, CaO 0.65%-5.85%, MgO 0.57%-6.49%, K2O 1.95%-6.26%, Na2O 0.5%-3.76%, and TiO2 0-0.78%; the ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the green body layer is ≥0.
350.
2. The environmentally friendly, easy-to-process ceramic slab with low crystalline silica content according to claim 1, characterized in that: The glass phase in the preform layer comprises 69.0%-88.5% by weight.
3. The environmentally friendly, easy-to-process ceramic slab with low crystalline silica content according to claim 1, characterized in that: The percentage of silica (SiO2(E)) in the glass phase of the preform layer, exceeding the stoichiometric ratio of feldspar, is ≥27.0%.
4. The environmentally friendly, easy-to-process ceramic slab with low crystalline silica content according to claim 1, characterized in that: The fracture toughness of the environmentally friendly, easy-to-process ceramic slab with low crystalline silica content is ≥1.2 MPa·m. 1 / 2 The modulus of fracture is ≥50MPa.
5. The environmentally friendly, easy-to-process ceramic slab with low crystalline silica content according to claim 1, characterized in that: The environmentally friendly, easy-to-process ceramic slab with low crystalline silica content is processed according to the processability test method in the T / CBCSA 40—2021 "Ceramic Slab" standard, and achieves first-level processability.
6. A method for producing environmentally friendly, easily processed ceramic slabs with low crystalline silica content, characterized in that, Includes the following steps: S1, Preparation of ceramic slab slurry: First, weigh the raw materials for preparing ceramic slab slurry, then mix the weighed raw materials for preparing ceramic slab slurry, then add water, pebbles and additives and ball mill them through a ball milling system, and finally sieve to obtain ceramic slab slurry. S2, Preparation of ceramic slab blank powder: The ceramic slab blank slurry obtained in step S1 is spray-dried and then aged to obtain ceramic slab blank powder for pressing ceramic slab blanks. The chemical composition of the ceramic slab blank powder, by dry weight percentage, includes: SiO2 55.68%-62%, Al2O3 20.5%-27.36%, Fe2O3 0-2.88%, CaO 0.48%-6.52%, MgO 0.47%-4.8%, K2O 1.44%-4.8%, Na2O 0.33%-2.8%, loss on ignition 4%-7%, and the balance being impurities. S3, Preparation of ceramic slab blank: The ceramic slab blank powder obtained in step S2 is pressed into shape by molding equipment and dried to obtain ceramic slab blank; S4, Decoration of ceramic slab blank: The ceramic slab blank obtained in step S3 is glazed and inkjet printed, and then dried to obtain the decorated ceramic slab blank. S5, Firing of ceramic slab blank: The decorated ceramic slab blank obtained in step S4 is fired at high temperature to obtain a ceramic slab semi-finished product. The highest firing temperature of the high temperature firing is 1150-1250℃, the firing cycle is 55-150min, and the holding time at the highest firing temperature is ≥7min. S6, Post-processing of ceramic slab semi-finished product: The ceramic slab semi-finished product is post-processed to obtain a finished ceramic slab containing a green body layer and a decorative layer disposed on the upper surface of the green body layer. The phase composition of the green body layer is crystalline silicon dioxide SiO2 (C p The content, expressed as a percentage by weight, is ≤10%; In step S2, before spray drying the ceramic slab slurry obtained in step S1, the ceramic slab slurry is preheated. The phase composition of the green body layer, in terms of weight percentage, includes the following glass phase chemical composition: SiO2(A) 59.98%-67%, Al2O3 20.82%-27%, Fe2O3 0-2.64%, CaO 0.65%-5.85%, MgO 0.57%-6.49%, K2O 1.95%-6.26%, Na2O 0.5%-3.76%, and TiO2 0-0.78%. The ratio of n(CaO+MgO) / n(CaO+MgO+K2O+Na2O) in the glass phase of the green body layer is ≥0.
350.
7. The production method of environmentally friendly, easy-to-process ceramic slabs with low crystalline silica content according to claim 6, characterized in that: In step S1, the ball milling system is either an intermittent ball milling system or a continuous ball milling system; In step S6, the post-processing includes polishing, edge grinding, and application of nano-liquid.
8. The production method of environmentally friendly, easy-to-process ceramic slabs with low crystalline silica content according to claim 6, characterized in that: In step S1, the sieving is performed using an 80-150 mesh vibrating screen, the processing fineness of the ceramic slab slurry is 2.5%-3.5% residue on a 325 mesh sieve, the specific gravity is 1.68-1.74 g / ml, and the flow rate is 16-32 s using an NK-2 Iwata viscosity cup. In step S2, the moisture content of the ceramic slab powder is 5.5%-7.5%, and the particle size is 45%-55% residue on a 40-mesh sieve. In step S3, the pressing pressure of the molding equipment is 35-42 MPa; In step S6, the content of the glass phase in the phase composition of the preform layer is 69.0%-88.5% by weight, and the molar percentage of silicon dioxide SiO2(E) in the glass phase of the phase composition of the preform layer exceeding the stoichiometric amount of feldspar is ≥27.0%.
Citation Information
Patent Citations
Large ceramic sheet and manufacturing method therefor
JP2018168055A